(untitled) (Journal of Economic Research & Business Administration, 2017)
The article considers the role of innovative activity of small business in the structure of GDP. Nowadays when the economic situation in the world is unstable, different countries are trying to reach economic growth by different effective ways. One of such tools is developing innovative activity of small and medium entrepreneurship in the structure of GDP. The article also considers the experience of developed countries, because the share of SME in GDP is more than 50%. Accordingly, one of the main aims of our Government is to provide witj necessary resources all entrepreneurs who are eager to get state support. On the other hand, the comparative analysis of different regions and cities of Kazakhstan by their innovative activity in small business is done.